Economic and Sociocultural Barriers to the Continuation of Studies of Indigenous Papuan Students at Musamus University - Jua, Selestina Kostaria; Simbolon , Merta; Reski, Andi; Uskenat , Kristina (Muhammadiyah University of Makassar, 2026)
This study aims to explore the external barriers faced by Papuan students at Musamus University in completing their studies. The phenomenon of low academic performance and high dropout rates forms the backdrop for this research. Using a descriptive qualitative method over a three-year period, data were collected through observation, distribution of questionnaires, and in-depth interviews with students. The results indicate that students face multidimensional, interrelated external barriers. First, family financial instability forces students to work, live with relatives in overcrowded housing far from campus, commute on foot, and neglect safety and health to save on living expenses. Second, learning disruptions impact concentration levels and lead to inefficiencies in academic activities outside of class hours. This burden is particularly severe for female students due to domestic responsibilities and child-rearing duties. Third, low family educational literacy results in a lack of social control and financial, functional, and emotional support for students. This study recommends policy synergy through the provision of student dormitories, integrated transportation, and psychosocial support programs to create a more adaptive educational ecosystem for indigenous Papuan students.